Managing Data Orchestration and Integration at Scale - Poskitt, Kevin; Poskitt, Kevin; Gatling, Ginger (O'Reilly Media, Inc., 2020)
Why is data integration still a challenge today? And what does data orchestration mean? In this report, Kevin Poskitt and Ginger Gatling from SAP provide in-depth examples that show how companies have evolved from using data integration to data orchestration. By combining streaming data with application data, external data, and social data, data engineers and developers can achieve trusted business outcomes. You'll learn how to use R, Python, TensorFlow, Apache Kafka, and other open source tools--either to extract data from SAP to put into a data lake or to orchestrate and integrate massive data volumes across complex landscapes. If you're ready to close the gap between the data experts on the SAP team and the development professionals in your company, this guide is indispensable. You'll examine: Data integration challenges--and why data orchestration needs to evolve The business imperative for data integration The reality of hybrid data management today Examples of how companies can use OS technologies for data integration The challenges of managing multiple open source stacks How to orchestrate integration and processing across OS tools while scaling across enterprise apps How to leverage OS technologies with SAP Data Intelligence How to address tool and data sprawl when using multiple tools and engines Complex data orchestration examples Machine learning within data orchestration.